Effect of Tertiary and Secondary Phosphines on Low‐Temperature Formation of Quantum Dots1. Issue 18 (25th March 2013) - Yu, Kui; Liu, Xiangyang; Zeng, Qun; Leek, Donald M.; Ouyang, Jianying; Whitmore, Kenneth Matthew; Ripmeester, John A.; Tao, Ye; Yang, Mingli
<x xml:space="preserve">Abstract</x> Getting to the TOP of things: The coordination of tri‐n‐octylphosphine (TOP) instead of diphenylphosphine (DPP) to cadmium oleate (Cd(OA)2) reveals how tertiary and secondary phosphines enhance the yield and reproducibility of the synthesis of nanocrystals by shifting the equilibrium of the reaction to the right (see picture). High Cd‐to‐Se and Se‐to‐TOP feed molar ratios facilitate the formation of SeDPP by way of Se exchange from TOP to DPP.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>